Patterns of Termite Diversity and Their Ecological Associations with Dipterocarpaceae in the Soraya Research Station, Leuser Ecosystem, Indonesia - Iqbar Iqbar; Djufri Djufri; Syaukani Syaukani; Darusman Darusman (Leuser Journal of Environmental Studies, 2026)
This study aimed to assess termite diversity and habitat distribution at the Soraya Research Station (SRS), analyze ecological associations between termite species and Dipterocarpaceae, and identify key interaction types and their ecological roles in forest succession. Termite sampling was conducted using a standardized belt transect method across 50 subplots (0.5 ha). A total of 48 termite species from 2 families and 17 genera were recorded, with Termitidae (43 species) being the dominant family. Termite distribution was strongly associated with decomposing substrates, particularly fallen logs, while living trees showed high resistance to colonization. Despite the dominance of Dipterocarpaceae, only 10.4% of termite taxa interacted directly with these trees, and 92,1% of examined Dipterocarpaceae structures showed no active colonization. Specific interactions identified included neutral associations (Hospitalitermes hospitalis), opportunistic pest (Nasutitermes roboratus), and specialized decomposers (Coptotermes curvignathus, Macrotermes malaccensis, and Pericapritermes samarangi). The high termite diversity indicates significant ecological recovery at SRS. Termite-host interactions are primarily governed by substrate quality and decomposition stages rather than host identity, highlighting the effective structural and chemical defenses of living Dipterocarpaceae in secondary tropical forests.